Advanced Construction Technology and Research of Deep-Sea Tunnels - Mei, Guoxiong; Xu, Zengguang; Zhang, Fei.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book focuses on cutting-edge construction techniques for deep-sea tunnels. A world leader in construction technology for deep-sea tunnels and large undersea engineering structures, China has in these years completed several world-renowned undersea tunnel projects, such as the undersea tunnel connecting Shenzhen and Zhongshan, and the Shantou Bay undersea tunnel. The nation also boasts mature technology and enviable scientific research achievements in large-scale shield technology and deep-sea soil hydrostatic surveying. This book intends to provide a review of relevant studies on deep-sea tunnel construction for civil engineers around the globe and equip scholars in related fields of research with a deeper insight into this domain through comprehensive analyses of real-world engineering cases and the most up-to-date research results. The topics of this book include but are not limited to the following: 1. Deep-sea survey technology and equipment. 2. Complex load characteristics and numerical simulation technology in the marine environment. 3. Key technology of immersed tube and shield tunnel construction. 4. Deep-sea construction equipment and safety assessment methods. 5. Deep-sea positioning, measurement and control technology.
Deep-sea survey technology and equipment -- Complex load characteristics and numerical simulation technology in marine -- Key technology of immersed tube and shield tunnel construction -- Deep-sea construction equipment and safety assessment methods.-Deep-sea positioning, measurement and control technology.
Keywords: Underground construction; Offshore structures; Marine engineering; Underground Engineering and Tunnel Construction; Offshore Engineering; Marine Engineering